A new record of recently discovered crayfish, Austropotamobius torrentium (Shrank, 1803), in Turkey - Harlioglu, Muzaffer Mustafa; Guner, Utku (Conseil Superieur de la Peche, 2007)
After the occurrence of Austropotamobius torrentium in the Velika River in European Turkey, investigations to observe the distribution of crayfish species close to the Velika River have been carried out. The present observations showed that the distribution of A. torrentium expanded in European part of Turkey. In the summer of 2006, A. torrentium was found in the Madara. Brook, but the abundance of A. torrentium in this brook was very low in comparison to the Velika River. Under the light of present observations, it could be concluded that besides the limited exploitation interest of A. torrentium in Turkey, this crayfish species increases its distribution in European Turkey, and more research should be carried out on its distribution and its either native or introduced presence in Turkey.
Keywords: Austropotamobius torrentium; crayfish; distribution; Madara brook; Turkey